2007
DOI: 10.1074/jbc.m605904200
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Inhibits Transforming Growth Factor β-Induced Apoptosis in Glomerular Mesangial Cells via Smad7 Deacetylation

Abstract: SIRT1, a class III histone deacetylase, is considered a key regulator of cell survival and apoptosis through its interaction with nuclear proteins. In this study, we have examined the likelihood and role of the interaction between SIRT1 and Smad7, which mediates transforming growth factor ␤ (TGF␤)-induced apoptosis in renal glomerular mesangial cells. Immunoprecipitation analysis revealed that SIRT1 directly interacts with the N terminus of Smad7. Furthermore, SIRT1 reversed acetyl-transferase (p300)-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(166 citation statements)
references
References 34 publications
8
153
1
Order By: Relevance
“…SIRT1 has been reported to deacetylate the lysine residues of a number of nuclear proteins, such as p53 (Yuan et al., 2011), NF‐κB (Salminen & Kaarniranta, 2009), PGC‐1a (Amat et al., 2009), CBP/p300 (Das, Lucia, Hansen & Tyler, 2009), and forkhead family proteins (Brunet et al., 2004). Several recent studies demonstrated that Sirt1 could inhibit TGF‐β signaling and ameliorate fibrosis (Huang et al., 2014; Kume et al., 2007; Zerr et al., 2014). In this study, we found that aging suppressed SIRT1 activity, increased TGFβ and MMP expressions, and induced fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 has been reported to deacetylate the lysine residues of a number of nuclear proteins, such as p53 (Yuan et al., 2011), NF‐κB (Salminen & Kaarniranta, 2009), PGC‐1a (Amat et al., 2009), CBP/p300 (Das, Lucia, Hansen & Tyler, 2009), and forkhead family proteins (Brunet et al., 2004). Several recent studies demonstrated that Sirt1 could inhibit TGF‐β signaling and ameliorate fibrosis (Huang et al., 2014; Kume et al., 2007; Zerr et al., 2014). In this study, we found that aging suppressed SIRT1 activity, increased TGFβ and MMP expressions, and induced fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in chromatin regulation through histone deacetylation (discussed below; Figure 3), SirT1 has additional roles as a sensor of the metabolic status of the cell. These functions depend largely on the deacetylation of non-histone proteins that can be divided into three groups: transcription related factors: p53, PGC1-a, PPRg, the FOXO family of factors, MyoD, nuclear factor-kB (NF-kB), Bcl6, TAF I 68, E2F1, p73 and others, chromatin-related enzymes: the HATs p300 and P300/CBP-associated factor (PCAF), the corepressors NcoR/SMRT, the DNA-dependent protein kinase subunit Ku80, with the third group being signaling factors like Smad7 (Luo et al, 2001;Muth et al, 2001;Vaziri et al, 2001;Fulco et al, 2003;Brunet et al, 2004;Cohen et al, 2004;Motta et al, 2004;Picard et al, 2004;Yeung et al, 2004;Bouras et al, 2005;Rodgers et al, 2005;Wang et al, 2006;Dai et al, 2007;Kume et al, 2007).…”
Section: Class III Functionsmentioning
confidence: 99%
“…38 Consistent with these considerations, SIRT1 has been reported to interact and deacetylate SMAD7, which is an auto-inhibitory downstream molecule of TGFβ signaling. 74 A caveat to the identification of SIRT1-modulated genes is that SIRT1 appears to be a context/signal-dependent regulator of cellular responses. While the gene expression profile in SIRT1-deficient endothelial cells clearly support a role of SIRT1 in the transcriptional control of endothelial homeostatic functions, it remains to be determined whether the gene expression changes observed in the microarray analysis performed under basal conditions reflect the entire signaling network of SIRT1 in vascular homeostasis.…”
Section: Gene Targets Of Sirt1 In Endothelial Cellsmentioning
confidence: 99%